Without conditions attached: Towards making participation rights a reality for all Scotland’s children and young people. (Concept: The Journal of Contemporary Community Education Practice Theory, 2013)
The UK government became a signatory to the UNCRC on 19th September 1990. Eighteen years on, it can be argued that the universality of children and young people’s human rights, in particular their participation rights, remains, more of an ideology than a global reality. The following article looks at the current understanding and positioning of children and young people’s participation rights and seeks to provide a working definition and define a common approach for those working to make participation rights a reality for all Scotland’s children and young people.